2016
DOI: 10.17795/zjrms-6671
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Doses of Oral Midazolam for Pre Operation Sedation of Children

Abstract: Background: One of the major problems in pediatric surgery is anxiety and fear of separation from parents. Objectives: We studied the efficacy of different doses of oral midazolam for pre operation sedation of children. Patients and Methods:In this randomized, double-blinded clinical trial, 120 children aged 1 -8 years were enrolled in the study .The children were randomly assigned to one of 4 groups and received orally 0.5 mg/kg (group A), 0.8 mg/kg (group B), 1 mg/kg (group C), 0mg/kg (group D) of injectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Combining the documentation by Beirami et al with the report of Sheta et al 0.75 mg/kg oral midazolam empirically is associated with minimal or no causation of deep sedation. 4,13 In the two groups of this study, 0% deep sedation was observed supporting Beirami et al and of Sheta et al 4,13 Excellent sedation is critical to achieving zero agitation level and circumventing the attendant short term and long term sequelae of preoperative anxiety in children. The evidence that children aged 1 to 5 years exhibit the highest level of separation anxiety, and the efficacy of oral midazolam premedication in decreasing the incidence of preoperative and emergence agitation among children has been documented.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Combining the documentation by Beirami et al with the report of Sheta et al 0.75 mg/kg oral midazolam empirically is associated with minimal or no causation of deep sedation. 4,13 In the two groups of this study, 0% deep sedation was observed supporting Beirami et al and of Sheta et al 4,13 Excellent sedation is critical to achieving zero agitation level and circumventing the attendant short term and long term sequelae of preoperative anxiety in children. The evidence that children aged 1 to 5 years exhibit the highest level of separation anxiety, and the efficacy of oral midazolam premedication in decreasing the incidence of preoperative and emergence agitation among children has been documented.…”
Section: Discussionsupporting
confidence: 78%
“…4 Similarly Beirami et al documented that undue sedation occurred in their group C subjects following the administration of 1 mg/kg oral midazolam. 13 Inferentially, a dose of 0.75 mg/kg or 0.8 mg/kg of injectable midazolam given orally as premedication, when compared to a 0.5 mg/kg dose, provided a rapid onset of a more desirable sedation, while a dose of 1.0 mg/kg produced an undue over sedation, thereby, posing threat of more harm than benefit in a proportion of children. Combining the documentation by Beirami et al with the report of Sheta et al 0.75 mg/kg oral midazolam empirically is associated with minimal or no causation of deep sedation.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous relevant literature and our preliminary trials 23 , we choose 0.5 mg·kg −1 as constant dose of midazolam oral solution (10 ml: 20 mg, Yichang Humanwell, Inc., YiChang, HuBei; SFDA No. H20213321), the initial dose of intranasal esketamine is 1 mg·kg −1 as followed (2 ml: 50 mg, Jiangsu Hengrui Medicine; SFDA No.…”
Section: Methodsmentioning
confidence: 99%